2011
DOI: 10.1038/aps.2011.147
|View full text |Cite
|
Sign up to set email alerts
|

Huperzine A derivative M3 protects PC12 cells against sodium nitroprusside-induced apoptosis

Abstract: Aim: To investigate the effects of M3, a derivative of huperzine A, on the apoptosis induced by sodium nitroprusside (SNP) in PC12 cells. Methods: Cell viability was detected using MTT method. Apoptosis was examined with annexin V/prodium iodide (PI) stain. The levels of reactive oxygen species (ROS) were measured using fluorophotometric quantitation. The amount of malonaldehyde (MDA) was determined with MDA detection kits. The expression of caspase-3 and Hsp70 were analyzed using Western blotting. Results: Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Additional studies are necessary to reveal which components are responsible for antioxidative properties of the selected fractions, and to determine the exact mechanism of their antioxidative activity. It was previously suggested that HupA possesses potent antiapoptotic, neuroprotective and antioxidative properties [34,43,51,52,56]. Our study demonstrated that this alkaloid is not a direct scavenger of free radicals, and other mechanisms are responsible for its antioxidative potential.…”
Section: Discussionmentioning
confidence: 44%
“…Additional studies are necessary to reveal which components are responsible for antioxidative properties of the selected fractions, and to determine the exact mechanism of their antioxidative activity. It was previously suggested that HupA possesses potent antiapoptotic, neuroprotective and antioxidative properties [34,43,51,52,56]. Our study demonstrated that this alkaloid is not a direct scavenger of free radicals, and other mechanisms are responsible for its antioxidative potential.…”
Section: Discussionmentioning
confidence: 44%
“…Growth factors and mechanical cues affect peripheral nerve repair. Using cultured dopaminergic sympathetic ganglion neuron cells (PC12 cells treated with M3 and NGF) [462,463], vibration from 7-100 Hz enhanced neurite outgrowth when compared to NGF alone (Figure 3) [224,225]. Thereby, Piezo1 is imporant for axon growth because its knockdown induced aberrant growth and pathfinding errors [464].…”
Section: Peripheral Nerve Repairmentioning
confidence: 99%
“…Interestingly, the transformed products, huptremules A–D ( 1 – 4 ), featured unusual sesquiterpenoid–alkaloid hybrid structures that integrated the characteristics of fungal metabolites (tremulane sesquiterpenoids) and the exogenous substrate (hupA). 8α,15α-Epoxyhuperzine A ( 5 ), the known hupA derivative reported to protect PC12 cells against SNP-induced apoptosis, was obtained with a yield (>27%) higher than reported . The AChE inhibitory activities of 1 – 5 were significantly lower than that of hupA (Table ).…”
Section: Resultsmentioning
confidence: 97%